USE OF SOCIAL NETWORKS AND ACADEMIC PERFORMANCE IN EXACT SCIENCES IN UNIVERSITY STUDENTS. - Ph.D. Irma Leticia Chávez Márquez (International Journal of Research Science and Management, 2017)
The increase use of social networks gives way to new didactic strategies in university students. The objective of the research was to analyze the relationship between the use of the social network Facebook and academic performance in the subject Statistics in university students. The way the research was descriptive and correlational between the variables (use of social networks and academic performance). The research focus was mixed, applied type, the design was quasi-experimental. The research was carried out in the Facultad de Contaduría y Administración of the Universidad Autónoma de Chihuahua. The unit of analysis were students enrolled in the subject of Statistics. The sample size was 174 students. It was validated with a Cronbach alpha coefficient of 0.847. The main results indicate when we used the social network Facebook, we observed a better academic performance. As we had a greater participation in the social network Facebook, the final semester grade was best.It is necessary to continue with lines of research to follow up on the topic dealt with, both in the results obtained in the long term with the formal implementation of the use of social networks, and in the possible problems generated by its use.